Detached-Eddy Simulation of UH-60A Airloads using an Immersed Boundary Method - Park, J.H.; Linton, D.; Thornber, B. (My University, 2023)
The complete helicopter configuration of UH-60A Black Hawk in forward flight is numerically studied using an immersed boundary method and an actuator surface model. Detached-eddy simulation is conducted where the UH-60A fuselage is represented by the immersed boundary method, while the main and tail rotors are modeled using the actuator surface model. The low-speed case (flight counter 8513) from the UH-60A Airloads Program by NASA and the U.S. Army is considered. This case poses challenges such as significant blade-vortex interaction and rotor-airframe interaction. The validation of the test case is conducted for both isolated main rotor and full configurations, and the results are compared with flight test measurements and computational data from the literature. The main rotor blade airload data show excellent agreement with the reference data. The fuselage effect is observed in the inboard stations of the main rotor. The surface pressure data over the centerline of the fuselage, vertical stabilizer, and horizontal stabilator are presented. Qualitative data demonstrate massive flow separation from subcomponents of the fuselage that are often not included in computational fluid dynamics simulations. It also features significant main rotor-tail rotor interactions. The computational effort for three grid levels of each test case is provided.
Keywords: Aerodynamics